2013
DOI: 10.1371/journal.pone.0073815
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Alpha-Melanocyte Stimulating Hormone with Conventional Antibiotics against Methicillin Resistant Staphylococcus aureus

Abstract: Our previous studies revealed that alpha-melanocyte stimulating hormone (α-MSH) is strongly active against Staphylococcus aureus (S. aureus) including methicillin resistant S. aureus (MRSA). Killing due to α-MSH occurred by perturbation of the bacterial membrane. In the present study, we investigated the in vitro synergistic potential of α-MSH with five selected conventional antibiotics viz., oxacillin (OX), ciprofloxacin (CF), tetracycline (TC), gentamicin (GM) and rifampicin (RF) against a clinical MRSA stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 55 publications
1
35
0
Order By: Relevance
“…Studies are being conducted in our laboratory to test this hypothesis. Such a strategy could be immensely promising in the current scenario of continuous emergence of resistant microorganisms and antibiotic crisis [ 31 , 32 ]. Oxidative stress and inflammation often go together with bacterial infections [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies are being conducted in our laboratory to test this hypothesis. Such a strategy could be immensely promising in the current scenario of continuous emergence of resistant microorganisms and antibiotic crisis [ 31 , 32 ]. Oxidative stress and inflammation often go together with bacterial infections [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of host-derived peptides or their mimics with direct bactericidal activity along with other essential cellular targets present their candidature towards optimization as antibacterial leads 3 37 38 . Our previous studies have shown that the neuropeptide α-MSH and its smaller fragments i.e., α-MSH(6–13) and α-MSH(11–13) have potent activity against S. aureus , MRSA and several clinical strains of S. aureus in micromolar concentration range 22 23 24 25 26 . Recently, in an elegant attempt to modify the activity of α-MSH(6–13), Grieco et al .…”
Section: Discussionmentioning
confidence: 99%
“…In the present work minimum inhibitory concentration (MIC) using broth micro-dilution technique following Clinical Laboratory Standards Institute (CLSI) guidelines could not be determined since similar to α-MSH the antibacterial activity of designed peptides got abolished in nutrient media used for the experiment 24 25 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the antimicrobial activity of FI3, 2 × 10 6 MSSA cells of mid exponential phase were taken as described elsewhere (26). The cells were incubated with varying concentration of FI3 i.e.…”
Section: Cell Viability Assaymentioning
confidence: 99%